Pension funding in a Keynesian model of growth. (January 2017) - Rada, Codrina
Abstract : This paper extends the post-Keynesian model of growth to reflect the feedback between pension funding, income distribution, and capital accumulation in an economy with overlapping generations. Different causal structures highlight factors that impact provision of pensions; conditions under which pension schemes promote economic and employment growth; and class conflict over the distribution of income. One key conclusion is that, as long as capital accumulation remains exogenous, policy and economic behavior of workers and retirees impact economic activity and sustainability of pension funding over transient paths but not at the steady state.